Characterization of Brass/Steel Plates Joined by Friction Stir Welding - K, Mariyappan.; K, Praveen; Kumar.S, Suresh; K, Kadambanathan.; S, Rajamanickam.; R, Vignesh. (International Journal of Engineering and Technology, 2018)
The aim of this study is to show the feasibility for butt joining dissimilar brass to austenitic stainless steel plates by Friction Stir Welding. In this study, the limited FSW parameters were employed. Metallurgical characterization like Scanning Electron Microscopy and Mechanical characterization like tensile test, Micro hardness is done to investigate the joint performance and the weld zone of dissimilar brass/steel joints. The tensile strength and micro hardness values are 20 MPa, 122 MPa and 157 MPa and 175 Hv, 196 Hv and 199 Hv for the table traverse speeds of 40 mm/min, 50 mm/min and 60 mm/min respectively. The tensile strength of dissimilar brass/steel joint was found to be lower than that of parent metals. The defect free brass/steel interfaces were seen by Scanning Electron Microscopy. It was illustrated that the stirred zone exposed to two main structures namely, recrystallized grains of brass and intercalated swirl and vortex-like structure which can be characterized both the recrystallized brass grains and steel layers. This work is one of the preliminary studies on the detailed examinations of the dissimilar brass/steel joined by Friction stir welding.Â